Tafsir Ayat Larangan Mendekati Zina pada Q.S. al-Isra [17]: 32: Perspektif Teori Mitologi Roland Barthes - Ida Fitri Nabila (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2024)
This study aims to look at the meaning of the symbols contained in QS. al-Isra verse 32 from the perspective of Roland Barthes' mythology theory. In the Qur'an, the prohibition of approaching adultery does not specifically mention the forms and types of actions that can be categorized as approaching adultery. This makes this verse has a broad meaning. The application of Barthes' mythology theory to this verse is considered to provide a new perspective on the interpretation of the prohibition by the times and interpretation. This research is a literature research using the Qur'anic text analysis approach with the foundation of Roland Barthes' mythology theory. The results of this study revealed that the myth contained in QS. al-Isra verse 32 among the wider community gave rise to new interpretations that continue to develop towards this verse. The acts of approaching adultery that are prohibited in this verse by using the lens of Roland Barthes' myth theory can be in the form of khalwat (being alone between men and women) and dressed but naked such as using open clothes, watching movies, pictures or magazines that contain nude, pornographic images and even songs containing bad invitations, dancing and hugging to various ways and types that bring together opportunities between men and women in digital space without any clear and justified purpose.